The stranger in the library - Gates, Eva, 1951- (Gates, Eva, 1951- Lighthouse library mystery, 2024)
When a reproduction of a famous painting is stolen from a traveling show of impressionist art, librarian Lucy is painted into a corner when a murder occurs, while Louise Jane is captivated by handsome art dealer, who might be the killer--and the person threatening to break her heart.